Parenting In Daycare To Strengthen Family Resilience Based On Islamic Law - Nasruddin, Muhammad; Santoso, Fattah S.; Sobirin, Sobirin; Suprianto, Agus (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
The high and even number of early marriages in Banyuraden Village, Gamping District, Sleman Regency deserves attention so that the problem of family disharmony can be minimized through parenting to strengthen the spiritual values ​​of Islam which are predominantly adhered to by residents in one of the daycares which is also a group for the Bina Keluarga Balita (BKB) activities. That is why Community Service with the theme of parenting family resilience based on Islam through Participation Action Research (PAR) was carried out. The implementation began with planning, licensing which also shared family resilience problems at one of the BKBs in the same village. Furthermore, an FGD was carried out on the Development of Islamic-based Family Resilience Materials related to the focus of BKB activities. Parenting was then carried out before the Evaluation was carried out. This community service activity can still be followed up by strengthening the parenting material on Islamic-based family resilience which has been adjusted to BKB activities.